Is order creation through disorder in additive manufacturing possible?. Issue 1 (1st January 2021) - Demoly, Frédéric; André, Jean-Claude
Abstract: Additive manufacturing is based on a deterministic principle of spatially localized material transformation. By using spatial energy resolution modes, it is thus possible to produce an object that meets a set of specifications in a step-by-step manner. This paper attempts to take the opposite view by examining whether it is interesting to use knowledge on "morphogenesis" (cf. Alan Turing) and other conceptual ideas of spontaneous self-organization to achieve a desired shape. This new and more systemic form of 3D/4D printing enables the self-assembly and establishment of elements (voxels) in various environments through the use of programmable or smart matter. The necessary convergence of interacting elements requires a related decisive activity, however, to the sign of unknown, indecision, complexity, unpredictable bifurcations, in short of scientific promise that cannot be robustly kept. Beyond this frame of generalized non-decidability—a form of abandonment of self-organization paradigm in favour of deterministic doctrines—, there are paths to partial success where desired spatial transformations can be created through (mastered?) disorder. The paper presents the conceptual bases of 3D self-organization with some illustrative examples. The objective is to highlight the interests of this disruptive vision with its realistic limits.